2016
DOI: 10.1556/650.2016.30403
|View full text |Cite
|
Sign up to set email alerts
|

Az ágy melletti ultrahangvizsgálat diagnosztikus lehetőségeinek vizsgálata a sürgősségi betegellátásban

Abstract: Bevezetés: Az ismeretlen etiológiájú kritikus állapotok közül a keringési elégtelenség (sokk) gyors differenciáldiag-nosztikája mindennapi kihívás a sürgősségi betegellátásban. A "Rapid Ultrasound in Shock" (RUSH) protokoll 2010 óta ismert, amelynek segítségével a négy sokkforma (kardiogén, disztributív, obstruktív, hypovolaemiás) elkülöníthe-tő. A módszerrel percek alatt megállapítható, hogy a háttérben milyen kórfolyamat (pericardialis tamponád, szívelég-telenség, tüdőembólia, hypovolaemia, vérzés, feszülő l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…34 Additionally, two studies were excluded following a QUADAS-2 assessment: one considered high risk for incorporation bias and imperfect gold standard bias, and another considered high risk for incorporation bias and double gold standard bias, both following author correspondence. 35 We excluded two conference abstracts due to insufficient data following unanswered requests for further information. 36,37 One trial was identified on clinicialtrials.gov for possible inclusion, but early results were not available.…”
Section: Search Resultsmentioning
confidence: 99%
“…34 Additionally, two studies were excluded following a QUADAS-2 assessment: one considered high risk for incorporation bias and imperfect gold standard bias, and another considered high risk for incorporation bias and double gold standard bias, both following author correspondence. 35 We excluded two conference abstracts due to insufficient data following unanswered requests for further information. 36,37 One trial was identified on clinicialtrials.gov for possible inclusion, but early results were not available.…”
Section: Search Resultsmentioning
confidence: 99%